A 3D luminescent Zn(ii) MOF for the detection of high explosives and the degradation of organic dyes: an experimental and computational study. Issue 43 (24th October 2017) - Jin, Jun-Cheng; Wu, Jian; He, Yong-Xiang; Li, Bao-Hong; Liu, Jian-Qiang; Prasad, Rajendra; Kumar, Abhinav; Batten, Stuart R.
Abstract : A 3D uncommon porous MOF1 with a 4-c lonsdaleite (lon ) topology based on binuclear Zn clusters behaves as a fluorescent chemosensor and a photocatalyst. Abstract : A new metal–organic framework, formulated as {[Zn2 (L)(DMF)3 ]·2DMF·2H2 O} (1 ), has been synthesized using a symmetrical rigid carboxylate ligand terphenyl-3, 3′′, 5, 5′′-tetracarboxylic acid (H4 L). Single-crystal X-ray diffraction analysis shows that1 possesses a 3D uninodal 4-c lonsdaleite (lon ) topology based on binuclear Zn clusters.1 behaves as a fluorescent chemosensor for highly selective and sensitive detection of Fe 3+ /Fe 2+ ions, 2, 4-dinitrophenol (2, 4-DNP), p -nitrophenol (PNP) and 2, 4, 6-trinitrophenol (TNP). Furthermore, the photocatalytic properties of1 for degradation of methyl violet (MV) and Rhodamine B (RhB) have been explored. The possible emission quenching of1 in the presence of aromatic compounds has been addressed by theoretical calculations and the photocatalytic activity of1 against organic dyes has been addressed using density of states (DOS) calculations.